2009
DOI: 10.1111/j.1600-0838.2009.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physical activity on sickness absence

Abstract: The aim of this study was to examine whether the volume and intensity of physical activity are associated with subsequent sickness absence spells of different lengths, and how much of these associations can be explained by socioeconomic position, body mass index (BMI) and physical health functioning. Baseline data were collected by questionnaire surveys in 2000-2002 among 40-60-year-old employees of Helsinki City (n=6465, 79% women). Sickness absence data were derived from the employer's registers (mean follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 23 publications
9
74
2
4
Order By: Relevance
“…One study suggests that high leisure-time physical activity is associated with a lower risk of sickness absence, whereas high occupational activity increases the risk (Holtermann et al, 2012). Some studies suggest that vigorous physical activity is important in preventing sickness absence (Lahti et al, 2010b;Proper et al, 2006). Previous studies on various health outcomes also suggest that vigorous activity may provide additional health benefits to moderate intensity activity (Janssen and Ross, 2012;Lahti et al, 2010a, in press;Lee and Paffenbarger, 2000;Samitz et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…One study suggests that high leisure-time physical activity is associated with a lower risk of sickness absence, whereas high occupational activity increases the risk (Holtermann et al, 2012). Some studies suggest that vigorous physical activity is important in preventing sickness absence (Lahti et al, 2010b;Proper et al, 2006). Previous studies on various health outcomes also suggest that vigorous activity may provide additional health benefits to moderate intensity activity (Janssen and Ross, 2012;Lahti et al, 2010a, in press;Lee and Paffenbarger, 2000;Samitz et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…walking/brisk walking) and 3. vigorously active (at least 14 MET-hours/week including vigorous physical activity i.e. jogging/running) (Lahti et al, 2010b). These three groups at the baseline and at the follow-up yielded nine groups describing changes over time in leisure-time physical activity from one group to another.…”
Section: Leisure-time Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a relationship between leisure-time PA and absenteeism -it has been determined that vigorous PA significantly reduces absenteeism due to sickness (13). It has also been shown that musculoskeletal and cardiovascular diseases -diseases in which PA has a significant preventive role -are among the main causes of absenteeism, permanent disability, and early retirement (14).…”
mentioning
confidence: 99%
“…Wyniki niektórych badań pokazują, że duże obciążenie fizyczne w miejscu pracy wcale nie oznacza poprawy zdolności funkcjonalnych i motorycznych (6), a wysoka zawodowa aktywność fizyczna może zwiększać ryzyko absencji w pracy (wyznacznik globalnego zdrowia) (11,13). Z kolei rosnący poziom aktywności fizycznej w czasie wolnym może to ryzyko zmniejszać (14).…”
unclassified